Does school average achievement explain the effect of socioeconomic status on math and reading interest? A test of the Information Distortion Model. (June 2021) - Parker, Philip; Sanders, Taren; Anders, Jake; Sahdra, Baljinder; Shure, Nikki; Jerrim, John; Cull, Nicola
Abstract: Based on the Information Distortion Model (IDM), we hypothesized higher academic interest among low socioeconomic (SES) Australian children compared to equally able high SES Australian children. We extend the IDM in two ways. First, the IDM is a model of school selection and thus empirical evidence of its effect needs to come from a model that controls for achievement prior to school selection. Second, the mechanism of the IDM is presumed to be the big-fish-little-pond-effect (BFLPE), which has not been tested. We used a longitudinal representative sample of first-year high-school students (age 12, N = 2507). We linked student high-school survey data to the whole of school and individual student administrative records of achievement from high-stakes national standardized tests in elementary and high-school. Our results were consistent with IDM for math interest but more mixed for reading interest, suggesting that additional processes may be in operation. Highlights: This study tested the Information Distortion Model (IDM). We considered the Big-fish-little-pond effect as the main IDM mechanism. Low SES children had higher numeracy interest than equally able high SES children. Results were more mixed for reading interest.